Dehydrated human amnion/chorion membrane allograft for preventing epidural fibrosis after laminectomy: an experimental rat model - Uçkun, Özhan Merzuk; Divanlıoğlu, Denizhan; Akdağ, Rıfat; Menekşe, Güner; Dalgıç, Ali; Belen, Ahmet Deniz (The European Research Journal, 2020)
Objectives: Post-laminectomy syndrome due to epidural fibrosis (EF) is a common cause of persistent low back pain after lumbar spinal surgery and is challenging for both surgeons and patients. The current experimental study aimed to investigate the effect of dehydrated human amnion/chorion membrane (dHACM) allograft for preventing EF formation following lumbar laminectomy.Methods: Sixteen Sprague–Dawley rats equally divided into two groups underwent lumbar laminectomy. Group A, the control group, underwent lumbar laminectomy with standard closure. Group B, the experimental group, additionally received epidural dHACM allografts during the procedure. After 45 days of follow-up, the rats were sacrificed, and the harvested tissues were histopathologically evaluated for EF.Results: Compared with Group A, Group B showed significantly less EF generation (p < 0.001), implying that dHACM allografts effectively prevent EF. Conclusions: This study demonstrated that dHACM can effectively reduce EF formation after spinal laminectomy in rats.